Nomi propri italiani nell'ungherese IV: Marchionimi - Fábián, Zsuzsanna (Verbum – Analecta Neolatina, 2002)
The article is the fourth part of a series analysing the lexicographical presence of Italian in Hungarian language: after names of persons places and institutions the Author focuses now on trade marks. She shows the specialities of this sector of the lexicon: the intentions of marketing, the lexicalization process and the high speed of changes. She provides a large range of examples, cathegorized by a linguistical tipology: abbreviations, derived and composed names, sintagmatical and phrasal ones.